Avaliação de desempenho de concessionárias de máquinas agrícolas: um estudo baseado no balanced scorecard - Bittencourt, Sandro Augusto Martins (2004)
Nowadays, the organizations are in front of the administration systems, quality programs and countless solutions diversity, which always seek to increase the competitiveness, like this, the actions promoted by the companies became drifted and best controlled by these tools. However, certain actions possess high degree of difficulty in the moment of their measure, because the traditional systems of administration worry too much about short term financial results, being unable to find out if a company social action contributes or not to the improvement of the result, in other words, they inform profit or damage precisely, however they fail in demonstrating why and which actions determine that acting. This work presents a case about an administration system model that predetermines the strategic actions of a companies group, taking them to manage their actions according to their philosophy, however, even possessing punctuation and classification scales, it fails in the moment of demonstrating to the administrators the results obtained with its effective use. Through a case study in one of the companies that uses the system, it is observed that the system, when integrated into the strategic administration system, denominated Balanced Scorecard, it becomes a quite wide and reliable managerial tool, because one determines the objectives of short and long period, financial and not financial actions, and the other measures the strategy and the result of these actions. It is concluded then, that the Balanced Scorecard use supplies the needs of companies acting measure, which possess a defined administration system, seeing its characteristic of analyzing financial and not financial actions, and the administration system facilitates the attainment of BSC, because it pre-determines in its pulp the objectives that orientate the process of acting evaluation.